Why Do Security Prices Change? A Transaction-Level Analysis of NYSE Stocks - Madhavan, Ananth; Richardson, Matthew; Roomans, Mark (Review of Financial Studies, 1997)
This article develops and tests a structural model of intraday price formation that embodies public information shocks and microstructure effects. We use the model to analyze intraday patterns in bid-ask spreads, price volatility, transaction costs, and return and quote auto-correlations, and to construct metrics for price discovery and effective trading costs. Information asymmetry and uncertainty over fundamentals decrease over the day, although transaction costs increase. The results help explain the U-shaped pattern in intraday bid-ask spreads and volatility, and are also consistent with the intra-day decline in the variance of ask price changes.